Separating Physics and Dynamics Grids for Improved Computational Efficiency in Spectral Element Earth System Models. (26th June 2021) - Hannah, Walter M.; Bradley, Andrew M.; Guba, Oksana; Tang, Qi; Golaz, Jean‐Christophe; Wolfe, Jon
Abstract: Previous studies have shown that atmospheric models with a spectral element grid can benefit from putting physics calculations on a relatively coarse finite volume grid. Here we demonstrate an alternative high‐order, element‐based mapping approach used to implement a quasi‐equal‐area, finite volume physics grid in E3SM. Unlike similar methods, the new method in E3SM requires topology data purely local to each spectral element, which trivially allows for regional mesh refinement. Simulations with physics grids defined by 2 × 2, 3 × 3, and 4 × 4 divisions of each element are shown to verify that the alternative physics grid does not qualitatively alter the model solution. The model performance is substantially affected by the reduction of physics columns when using the 2 × 2 grid, which can increase the throughput of physics calculations by roughly 60%–120% depending on whether the computational resources are configured to maximize throughput or efficiency. A pair of regionally refined cases are also shown to highlight the refinement capability. Plain Language Summary: Most atmospheric models use the same grid for dynamics (e.g., advection) and physics (e.g., clouds). For spectral element models the grid uses irregularly spaced points and the treatment of element edges can lead to grid imprinting bias. Previous studies have shown that using a regularly spaced physics grid in a spectral element model can alleviate the grid imprinting biases. This alternative physics grid can also reduce the computational cost of the model if the physics grid is coarser than the dynamics grid. This study presents a new approach for using a regularly spaced physics grid in a global spectral element model that additionally allows mesh refinement for regionally focused simulations. The use of a relatively coarse physics grid is shown to make the model faster without qualitatively degrading the simulated climate. Key Points: A method is presented for defining a finite volume physics grid in a spectral element model that allows for regional refinement The new method is shown to qualitatively preserve the model solution and effective resolution A relatively coarse physics grid increases the speed of physics by roughly 60 % –120 % depending on how the computational resources are configured